The “Timeline Debriefing Tool”: a tool for structuring the debriefing description phase - Secheresse, Thierry (Adv Simul (Lond), 2019)
Several recent literature reviews have been published with the aim to determine how to optimise a debriefing. A main element found in these reviews was the importance of structuring the debriefing. Within the steps usually outlined in the debriefing, the description phase allows participants to describe their recollections and establish a shared mental model of what happened during the simulation. The description phase is used in many debriefing models but how to realise this description remains unclear. We provide an original tool to ensure a highly structured description phase: the “Timeline Debriefing Tool”. The Timeline Debriefing Tool, or TDT, is constructed on visual support such as a whiteboard or a flipchart. It allows for a clear description phase, makes the process more dynamic, promotes exchanges between participants and establishes a clear and shared vision of the simulation in visual support which can be used by the instructor in the analysis phase. Moreover, the timeline allows participants to discover their performance gaps by themselves, thus beginning deeper cognitive processing in the participants’ mind and promoting reflection in the analysis phase.